Catalytic Activity for Oxygen Reduction Reaction on CoN2 Embedded Graphene: A Density Functional Theory Study. Issue 12 (1st January 2017) - Zhang, Jing; Wang, Yan; Wang, Yuanyang; Zhang, Mingang
Abstract : Metal-coordinated nitrogen-doped carbons are highly active in promoting oxygen reduction reaction (ORR). However, small changes within the structure can lead to significant differences in ORR activity. This work systemically studied the ORR behavior on three different CoN2 -graphene using density functional theory calculations. All the three catalysts showed high ORR activity. Especially, the CoN2 -G(A) exhibited higher ORR activity than CoN2 -G(B) and (C). On CoN2 -G(A), the ORR is a complete four-electron reduction. Two different four-electron pathways are facilitated. The H2 O2 -mediated four-electron pathway is unfavorable when electrode potential U > 0.20 V, however, the direct four-electron pathway is active up to a limiting potential of 0.64 V. The first reduction step, O2 -to-OOH is the limiting step, meanwhile, it has the largest activation barrier of 0.32 eV, acting as the kinetic and thermodynamic rate-determining step. On CoN2 -G (B) and (C), both the two-electron and four-electron pathways are favorable. But the direct four-electron pathway could be activated at a relatively high limiting potential (0.53 V and 0.62 V for CoN2 -G (B) and (C), respectively.) whereas the two-electron and H2 O2 -mediated four-electron pathways could be activated only at a low limiting potential.